"Sometimes Things Get Worse Before They Get Better": A Counter-Narrative of White Suburban School Leadership for Racial Equity. Issue 2 (3rd April 2019) - Irby, Decoteau J.; Drame, Elizabeth; Clough, Cynthia; Croom, Marcus
ABSTRACT: Elizabeth is a middle-class white woman and principal of Eagle Wings High School, a large, well-resourced, high-performing suburban high school. This manuscript uses a Critical Race Theory composite counterstory to analyze Elizabeth's experiences of racial conflict that resulted after she enacted equity reforms to address her school's history of racial inequity. We examine the manner in which Elizabeth's decision-making for students of color related to her racial meaning-making and identities and how the resistance Elizabeth faced was not merely from teachers or white parents, but also from within herself.